Atmospheric Practices: On Affecting and Being Affected. Issue 2 (May 2021) - Bille, Mikkel; Simonsen, Kirsten
This article reviews and discusses recent literature on affect by highlighting two central problems: the problem of distinction and the problem of transmission. To deal with these problems, we argue, literature within geography has turned from affect to affective atmospheres to emphasize the spatial and material aspects of affect. Yet in so doing, such literature has largely omitted the role of practices, which has simultaneously been studied in both other strands of geography and other social sciences. Simultaneously, little attention has been paid to the affective aspects of practices. This article seeks to combine the perspectives from these diverse fields. We argue for a need to understand the affective as engrained in the practices of attuning atmospheres. In this way, affect is not a noun with a clear ontological status; it only takes such status through verbal or adjectival forms as qualities of materialities connected to bodily practices of affecting and being affected. This necessitates that the lived body become an entry point for exploring how individuals actively are attuned and attune themselves and others through atmospheres.